A New and Easy Method to Determine the Energy Stored in Urban Areas: A Case Study of Mexico City - Martín Bonifacio-Bautista; Monica Ballinas; Victor L. Barradas (Urban Science)
Urban areas present different climates from those of their rural surroundings. Energy balance and especially energy storage play important roles in the resulting climate since more than 50% of the net radiation is absorbed in densely urbanized areas. A simple model of energy storage in the urban fabric is presented, fed with the air temperature of a given area and its thermal properties; it can estimate heat storage (QS) with good results. The proposed QST energy storage model was compared with QS results obtained from two sites in Mexico City, Escandón (objective hysteresis model, QSOHM) and ENP7 (residual, QSRES), and one site in Marseille, France (thermal mass scheme, QSTMS). The comparison between QST and QSOHM showed that r2 = 0.71, while in ENP7 (QN > 0), QSRES and QST were 116.5 Wm−2 and 142 Wm−2, corresponding to 49% and 60% of the QN, respectively. The results obtained using the QSTMS model in Marseille and QST in Escandón showed similar behavior, with RMSEs of 109 and 101 Wm−2, respectively, in a daily period. Although it is difficult to discern which method is better, it is possible to affirm that the presented method is quite accurate, easier to use, and inexpensive.